ANALISIS PERBANDINGAN FRAMEWORK BACKEND NODE.JS DAN SPRINGBOOT MENGGUNAKAN METODE GRAPHQL - barkah, affu; I Nyoman Yudi Anggara Wijaya; Nengah Widya Utami (ITB Ahmad Dahlan Jakarta, 2025)
As the demand for fast, responsive, and scalable web applications grows, API technologies have rapidly evolved. GraphQL offers efficient data management and transfer, with Node.js and Spring Boot being two widely used frameworks for its implementation. This study aims to compare the performance of GraphQL APIs built with these frameworks. Performance testing focused on response time, throughput, error rate, and concurrent user capacity, using dummy data under varying loads via Postman. Results show that under low loads (10 virtual users), both frameworks perform similarly. However, at higher loads (50 virtual users), Spring Boot demonstrates better performance with faster response time (514 ms vs. 1,766 ms), higher throughput (53.64 rps vs. 18.46 rps), and no errors, while Node.js records a 1.79% error rate. In Spike and Peak scenarios, Spring Boot consistently outperforms Node.js. These findings provide valuable insights for developers in selecting the most suitable framework based on application needs.